Búzaminták fungicid szermaradvány ellenőrzése és gombafertőzöttségének kimutatása - Soós, József; Fehér, László; Rigó, Krisztina; Tanács, Lajos (Acta Agraria Debreceniensis, 2002)
To protect crops with chemicals against different microorganisms are very important because residues of toxins could pollute infected grains. This could have the meaning of serious danger to the human and animal health. Similarly important is knowledge of details about presence or absence of any practically applied protective compounds. Experimental studies were performed on fungicide treated cereals of the Cereal Research Non-Profit Company, Szeged. Chromatographic methods were used (GC and some GC-MS) to find low level fungicide residues, microwave-assisted isolation of ergosterol was followed by HPLC to detect possible fungal infections and a more detailed microbiological analysis completed the work. Concerning the dry year 2000, no fungicides were found in the samples (by November), the ergosterol level was found to be less than 8 ppm, meaning good quality, coupled with an extremely low level of fungal infections. This was confirmed by direct microbiological testing. In comparison with the microbiological results from 1999, a negative difference can be recognized, most probably due to the rainy weather throughout the year.